Don't Label Me: A Qualitative Study of Patients' Perceptions and Experiences of Sedation During Behavioral Emergencies in the Emergency Department. (19th June 2017) - Yap, Celene Y. L.; Knott, Jonathan C.; Kong, David C. M.; Gerdtz, Marie; Stewart, Kay; Taylor, David M.
Abstract: Objectives: Behavioral emergencies are commonly seen in emergency departments (EDs). Acutely agitated patients can be difficult to manage and sedation may be required to decrease dangerous behavior and to ensure the safety of both the patient and the staff. While the experience of staff caring for this population has been reported, patients' experiences with their overall management remains unknown. We aimed to describe the perceptions and experiences of patients regarding the use of sedation during acute behavioral emergencies. Methods: Face‐to‐face semistructured interviews were conducted with adults aged 18 years or older, who had received parenteral sedative medication for the management of a behavioral emergency and were deemed capable to participate. The participants were asked about their experiences of receiving care in the ED during the episode and their perceptions of sedation. All interviews were transcribed verbatim and analyzed thematically. Results: Data saturation was reached after 13 interviews. Two broad themes emerged: trusting relationships and needs or wants following sedation. A trusting relationship is built through 1) confidence in care, 2) sedation as an appropriate treatment, 3) insight into own behavior, and 4) humane treatment. Four subthemes of needs or wants were identified: 1) empathy, 2) debrief, 3) addressing concerns, and 4) follow‐up. Conclusions: A trusting relationship was identified as crucial to minimize the negative impact of coercive measures used to manage behavioral emergencies. Participants expressed similar needs to patients presenting with medical problems. This study illustrates their needs for compassionate communication, adequate information about the treatment provided, and follow‐up care.